Research on the Integration and Evolution of Ideological and Political Education and Aesthetic Education in China (Journal of humanities and social sciences exploratio, 2026)
This paper aims to systematically review the complex evolution of the integration and mutual influence between ideological and political education and aesthetic education in the Chinese context from ancient times to the present, through the dual lenses of intellectual history and educational history, with a particular focus on the sinicization and contemporary practice of Marxist aesthetic views. The study first traces China's profound ideological lineage regarding the relationship between "beauty and goodness," distinguishing the ethical orientation of Confucianism's pursuit of "exhaustive goodness and beauty," the quest for spiritual freedom in Daoism and Zen Buddhism, and the impact of modern Western aesthetics. Building on this foundation, the paper's core contribution lies in an in-depth analysis of how Marxist aesthetic thought, particularly its discussions on "the all-round development of individuals," "labor creating beauty," and "art belonging to the people," has profoundly shaped the practical paradigm of integrating aesthetic education with ideological and political education in China since the 20th century. The study points out that this integration has undergone a transformation from classical "moral analogy," revolutionary-era "moral conveyance," to contemporary pursuit of "nurturing the heart." Through an examination of current policies on "curriculum-based ideological and political education" and "educating through beauty," this paper critically analyzes the risks of "simple political dependency" and "hollow entertainment" faced by the integration of the two in an educational environment dominated by instrumental rationality. Ultimately, the article argues that the relationship between ideological and political education and aesthetic education in China has demonstrated a dialectical developmental trajectory from "goodness dominating beauty," to "separation of beauty and goodness," and finally to "synergy between beauty and goodness." Its contemporary significance lies in drawing on the wisdom of Marxism and traditional culture to construct a new educational ecosystem rooted in Chinese soil that "nurtures goodness through beauty and establishes beauty through goodness," providing a profound historical legitimacy basis and innovative practical pathways for the fundamental task of fostering virtue through education.
Keywords: Ideological and political education; Aesthetic education; Marxist aesthetics; Relationship between beauty and goodness; Curriculum-based ideological and political education